PENGARUH KUALITAS LAYANAN DAN CITRA PERUSAHAAN TERHADAP KEPUASAN NASABAH PT. BANK PERKREDITAN RAKYAT GRACIA MANDIRI BEKASI TIMUR - Budiarto Nugroho; Iwan Kurniawan Subagja (Jurnal Manajemen Bisnis Krisnadwipayana, 2018)
In the current era of globalization the level of competition in the business world becomes increasingly tight. Many are doing small businesses that require capital, or small businesses that are developing to increase the ability of an increasing economy. This relates to one of the most important objectives and should be undertaken by all types of business: maintaining the viability of the company over a long period of time (going concern), business activities sometimes, visiting some things with competition to gain additional capital. This also makes it a challenge for bank companies to showcase their brand and quality of service that is superior and satisfactory to the purpose and number of customers. This study aims to describe the quality of service and corporate image to customer satisfaction PT. Bank Perkreditan Rakyat Gracia Mandiri Bekasi Timur. Samples and this research lied 100 respondents with sampling technique purposive sampling. The method of analysis used are description and regression analysis. The results showed that the quality of service and corporate image include customer satisfaction.